Gene expression changes in human iPSC-derived cardiomyocytes after X-ray irradiation. (2nd December 2018) - Becker, Benjamin V.; Majewski, Matthäus; Abend, Michael; Palnek, Andreas; Nestler, Kai; Port, Matthias; Ullmann, Reinhard
Abstract: Purpose: Radiation-induced heart disease caused by cardiac exposure to ionizing radiation comprises a variety of cardiovascular effects. Research in this field has been hampered by limited availability of clinical samples and appropriate test models. In this study, we wanted to elucidate the molecular mechanisms underlying electrophysiological changes, which we have observed in a previous study. Materials and methods: We employed RNA deep-sequencing of human-induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs) 48 h after 5 Gy X-ray irradiation. By comparison to public data from hiPSC-CMs and human myocardium, we verified the expression of cardiac-specific genes in hiPSC-CMs. Results were validated by qRT-PCR. Results: Differentially gene expression analysis identified 39 and 481 significantly up- and down-regulated genes after irradiation, respectively. Besides, a large fraction of genes associated with cell cycle processes, we identified genes implicated in cardiac calcium homeostasis ( PDE3B ), oxidative stress response ( FDXR and SPATA18) and the etiology of cardiomyopathy ( SGCD, BBC3 and GDF15 ). Conclusions: Notably, observed gene expression characteristics specific to hiPSC-CMs might be relevant regarding further investigations of the response to external stressors like radiation. The genes and biological processes highlighted in our study present promising starting points for functional follow-up studies for which hiPSC-CMs could pose an appropriate cell model when cell type specific peculiarities are taken into account.